2000
DOI: 10.1098/rspb.2000.1213
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and phylogenetic congruence between chloroplast and mitochondrial haplotypes inSilene vulgaris

Abstract: Both the chloroplast and mitochondrial genomes are used extensively in studies of plant population genetics and systematics. In the majority of angiosperms, the chloroplast DNA (cpDNA) and mitochondrial DNA (mtDNA) are each primarily transmitted maternally, but rare biparental transmission is possible. The extent to which the cpDNA and mtDNA are in linkage disequilibrium is argued to be dependent on the ¢delity of co-transmission and the population structure. This study reports complete linkage disequilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 35 publications
4
78
1
Order By: Relevance
“…In Drosophila simulans, for example, the genealogy of mtDNA reflects the spread of Wolbachia rather than the relatedness of populations as assessed by nuclear DNA (Ballard et al 2002). Similarly, cytoplasmic male sterility in plants can be caused by genes in mitochondria, and can spread rapidly via selection, dragging both mitochondrial and chloroplast genes along with it (Olson and McCauley 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila simulans, for example, the genealogy of mtDNA reflects the spread of Wolbachia rather than the relatedness of populations as assessed by nuclear DNA (Ballard et al 2002). Similarly, cytoplasmic male sterility in plants can be caused by genes in mitochondria, and can spread rapidly via selection, dragging both mitochondrial and chloroplast genes along with it (Olson and McCauley 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Strict co-inheritance of genomes is expected to generate congruent phylogenetic histories between genes in different genomes, whereas the absence of congruence implies at least somewhat independent histories (Desplanque et al 2000;Olson and McCauley 2000). Pairwise partition-homogeneity tests (Farris et al 1994) indicated incongruence between the pairwise histories of matK and atp1 (P ¼ 0.003), matK and atp9 (P ¼ 0.001), and atp1 and atp9 (P ¼ 0.001).…”
Section: Reassociation and Recombinationmentioning
confidence: 99%
“…However, studies of species wherein multiple CMS genes have been identified have shown that CMS variants are not allelic, but rather each is constructed from different sets of genes to create a novel chimeric open reading frame (Schnable and Wise 1998). Nonetheless, some researchers have posited that since the mitochondrial genome is inherited as a single linkage unit and the chloroplast and mitochondria are co-inherited, these genomes may harbor signals of past balancing selection or epidemics via hitchhiking (Olson and McCauley 2000;Ingvarsson and Taylor 2002;Cho et al 2004). …”
mentioning
confidence: 99%
See 2 more Smart Citations